Aktivitas Antioksidan Nanopartikel dari Ekstrak Daun Sembung (Blumea balsamifera L.): Antioxidant Activity of Nanoparticle Modified from Sembung Leaf (Blumea balsamifera L.) Extract - Saufani, Iza Ayu; Rahmi, Azimatur; Afriani, Tika; Zikirzi, Widi Urdatullah (Universitas Airlangga, 2024)
Background: Dietary antioxidants are essential to prevent free radical-induced cell damage and maintain the body’s physiological functions. Sembung leaves are rich in polyphenols, which are known to have substantial antioxidant activities. The antioxidant efficacy of Sembung leaves can be enhanced by nanoparticle size. Objectives: To examine the enhancement of antioxidant activity of Sembung leaf (Blumea balsamifera L.) extract modified into nanoparticles. Methods: The extract used was an ethyl acetate fraction extract. The fresh leaves of Sembung ware macerated in 96% ethanol for 24 hours. Ethanol, n-hexan, and ethyl acetate solvents were used to fractionate the ethanolic extract. The extract of the ethyl acetate fraction was modified into nanoparticles through the ionic gelation method. The nanoparticles comprised three formulations, F1 (0.25% chitosan and 10 ml NaTPP solution), F2 (0.50% chitosan and 20 ml NaTPP solution), and F3 (0.75% chitosan and 30 ml NaTPP solution). The antioxidant activity was assessed by lipid peroxidation using ferric thiocyanate (FTC) followed by the thiobarbiturat (TBA) method. A Spectrophotometer UV-Vis was used to analyse the % inhibition values of the samples. Results: The antioxidant activity assay on the sample of ethyl acetate fraction using the FTC method showed 31.25% inhibition, and using the TBA method indicated 17.34% inhibition. Meanwhile, the % inhibition was 23.77% and 40.43% in the nanoparticle sample with the FTC and TBA methods, respectively. Conclusions: This study revealed that nanoparticles of Sembung leaves can increase antioxidant activities. These findings offer potential applications in the development of existing antioxidant products.